In memory of Professor Halina Ryffert - HOJAN, Edward (Archives of Acoustics, 1996)
On 7th August 1996, Polish Acoustics suffered a great loss when Professor Halina Ryffert, a woman of merit in the acoustical community, passed away.She was born on 4th February 1916 in Bugulma (Russia) to a Polish family. Three years later they moved to Poznań (Poland), where Professor Ryffert lived and worked almost all her life.